Incidence and Biology of Corynespora cassiicola (Berk. & Curt.) Wei. disease of okra in Bangladesh - Ahmed, Fakhruddin Ali; Alam, Nazmul; Khair, Abul (Bangladesh Journal of Botany, 2014)
Eight commercial okra cultivars were evaluated to determine the magnitude of incidence of Corynespora cassiicola (Berk. & Curt.) Wei. Maximum and significant incidence of C. cassiicola was 14.86 in the cultivar BARI 1. In rest of the cultivars, the occurrence of this fungus was very poor to nil. Corynespora cassiicola appeared to be a minor pathogen for okra. Effects of temperature, pH and culture media on growth and sporulation of the fungus were investigated. Potato dextrose agar medium was found to be the most suitable for optimum growth and sporulation of this fungus at pH 7 and 25ºC. The conidial length significantly varied with the changes of pH. The correlation between pH and conidial length was found negative and highly significant. DOI: http://dx.doi.org/10.3329/bjb.v42i2.18028 Bangladesh J. Bot. 42(2): 265-272, 2013 (December)